Image forming system and image forming method
The use of a two-component developer with specific resistance and silicon content, combined with a (meta)acrylate coating resin, addresses charge leaks and enhances image quality in low-temperature and low-humidity environments by controlling toner charging and reducing defects.
Patent Information
- Application Number
- JP2023118727
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-31
AI Technical Summary
Existing image formation systems using aluminum alloys with high silicon content face issues with charge leaks and local image defects (black pochi) in low-temperature and low-humidity environments, leading to poor image quality.
The system employs a two-component developer with a carrier having a static resistance value between 10^8 Ω·cm and 10^12 Ω·cm and a silicon content in the aluminum alloy components of 0.6% to 12.6% or less, combined with a coating resin derived from (meta)acrylate, to control toner charging and reduce charge leaks.
This approach suppresses excessive toner charging and improves image concentration in low-temperature and low-humidity conditions, reducing local image defects and ensuring high-quality image formation.
Smart Images

Figure 2025015867000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an image forming system and an image forming method, and more particularly to an image forming system and an image forming method capable of suppressing excessive charging of a toner for developing an electrostatic image and obtaining a good image even in a low-temperature, low-humidity environment. [Background technology]
[0002] In recent years, there has been a demand for reducing the environmental impact of various members constituting the main body of an electrophotographic image forming apparatus.
[0003] One possible way to reduce the environmental burden is to use materials that emit less carbon dioxide per unit mass when manufacturing the various components mentioned above. For example, in the case of components that use aluminum alloys, the process of manufacturing aluminum from bauxite emits a large amount of carbon dioxide, which places a large burden on the environment. In contrast, by using aluminum alloys recycled from aluminum-containing waste materials, the process of manufacturing aluminum from bauxite can be eliminated. This can significantly reduce carbon dioxide emissions and lessen the environmental burden.
[0004] Regardless of whether they are recycled or not, elements other than aluminum are added to these aluminum alloys in order to control their physical properties and workability. In particular, silicon is added to various types of aluminum alloys because it affects heat resistance, thermal expansion, and workability.
[0005] As an example of using such silicon-containing aluminum alloys in components of electrophotographic image forming devices, for example, Patent Document 1 discloses an electrophotographic photoreceptor using a silicon-containing aluminum alloy for the support.
[0006] Moreover, Patent Document 2 discloses a developer carrier using an aluminum alloy containing silicon.
[0007] Incidentally, when producing aluminum alloys through recycling as described above, it is necessary to detect and remove impurities including silicon and adjust their contents.
[0008] However, because silicon is difficult to separate and remove, aluminum alloys produced through recycling contain more silicon than necessary, which means that when used in the above-mentioned components, they may not achieve the desired performance.
[0009] Therefore, there has been a demand for improvements that would enable desired performance to be achieved even when using a photoconductor and a developer carrier made of an aluminum alloy having a high silicon content as described above. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2022-132142 A [Patent Document 2] JP 2008-102502 A Summary of the Invention [Problem to be solved by the invention]
[0011] The present invention has been made in consideration of the above problems and circumstances, and the problem to be solved is to provide an image forming system and an image forming method that can suppress excessive charging of toner for developing electrostatic images and obtain good images even in low-temperature, low-humidity environments. [Means for solving the problem]
[0012] In order to solve the above problems, the present inventors have investigated the causes of the above problems and have found that the above problems can be solved by combining a support body of a photoconductor or a developing sleeve of the developer carrier, the aluminum alloy of which has a silicon content within a specific range, with a two-component developer, the static resistance value of the carrier of which is within a specific range, and have arrived at the present invention. That is, the above-mentioned problems of the present invention are solved by the following means.
[0013] 1. An image forming system using a two-component developer and an image forming apparatus equipped with at least one of a photoconductor using an aluminum alloy support or a developer carrier using an aluminum alloy developing sleeve, The static resistance value of the carrier contained in the two-component developer is 10 8 Ω cm or more, 10 12 Within the range of less than Ω cm, and The silicon content in the aluminum alloy forming at least the support of the photoreceptor or the developing sleeve of the developer carrier is in the range of more than 0.6 mass % and 12.6 mass % or less. 1. An image forming system comprising:
[0014] 2. The image forming system described in item 1, wherein the carrier is composed of carrier particles in which at least the surface of a core particle is coated with a coating resin, and the coating resin has a structure derived from a (meth)acrylate.
[0015] 3. The image forming system according to claim 2, wherein the coating resin contains at least one of carbon black, magnesium oxide and titanium dioxide.
[0016] 4. The image forming system described in item 2, wherein the exposed area ratio of the core particles to the surface of the carrier particle is within a range of 10.0 to 18.0% with respect to the surface area of the core particles.
[0017] 5. The image forming system described in item 1, characterized in that the silicon content is in the range of more than 0.8 mass % and not more than 12.6 mass % relative to the total amount of the aluminum alloy forming at least the photoconductor or the developing sleeve of the developer carrier.
[0018] 6. The image forming system described in item 2, wherein the coating resin has a structure derived from an alicyclic (meth)acrylate.
[0019] 7. The static resistance of the carrier is 10 8 ~10 10 2. The imaging system of claim 1, wherein the resistivity is in the range of Ω·cm.
[0020] 8. An image forming method using a two-component developer and an image forming apparatus equipped with at least one of a photoconductor using an aluminum alloy support or a developer carrier equipped with an aluminum alloy developing sleeve, The static resistance value of the carrier contained in the two-component developer is 10 8 Ω cm or more, 10 12 Within the range of less than Ω cm, and The silicon content in the aluminum alloy forming at least the support of the photoreceptor or the developing sleeve of the developer carrier is in the range of more than 0.6 mass % and 12.6 mass % or less. 1. An image forming method comprising: Effect of the Invention
[0021] The above-mentioned means of the present invention can provide an image forming system and an image forming method that can suppress excessive charging of a toner for developing an electrostatic image (hereinafter, also simply referred to as "toner") and obtain a good image even in a low-temperature, low-humidity environment.
[0022] Although the mechanism by which the effects of the present invention are expressed or the mechanism by which the effects of the present invention are acted upon has not been clarified, it is speculated as follows.
[0023] The image forming system of the present invention is an image forming apparatus using a two-component developer and at least one of a photoreceptor using an aluminum alloy support or a developer carrier using an aluminum alloy developing sleeve, and the static resistance value of the carrier contained in the two-component developer is 10 8 Ω cm or more, 10 12 The electrical conductivity of the aluminum alloy is in the range of less than Ω·cm, and the silicon content in at least the aluminum alloy forming the support body of the photoreceptor or the developing sleeve of the developer carrier is in the range of more than 0.6 mass % and not more than 12.6 mass %.
[0024] In the case of an aluminum alloy support for an electrophotographic photoreceptor, as the silicon content in the aluminum alloy increases, many coarse crystals (protrusions) due to the eutectic crystal of silicon and aluminum are present on the surface.
[0025] When an image is formed using a photoreceptor having such a support, an electric field is likely to concentrate at the convex portions, and charge leakage is likely to occur between the outermost surface of the photoreceptor and the photoreceptor support.
[0026] When such charge leakage occurs, the absolute value of the potential on the surface of the photoconductor becomes locally small, making it easier for localized image defects (black spots) to occur on the formed image.
[0027] On the other hand, even in a developer carrier having a developing sleeve made of an aluminum alloy, as the silicon content in the aluminum alloy increases, many coarse crystals (protrusions) due to the eutectic of silicon and aluminum appear on the surface.
[0028] When an image is formed using the developer carrying member as described above, the application of a voltage during development tends to cause leakage of electric charges between the protrusions on the surface of the developing sleeve and the surface of the photoconductor.
[0029] When such charge leakage occurs, the absolute value of the potential on the surface of the photoconductor becomes locally small, making it easier for localized image defects (black spots) to occur on the formed image.
[0030] As can be seen from the above, the causes are different between the support of the electrophotographic photoreceptor made of an aluminum alloy with a silicon content within a certain range and the developer carrier having a developing sleeve made of the aluminum alloy. However, they have in common the fact that localized image defects (black spots) occur due to charge leakage.
[0031] Therefore, both of them have in common the need for means to suppress charge leakage.
[0032] One possible method for suppressing charge leakage occurring between the outermost surface of the photoconductor and the photoconductor support is to reduce the absolute value of the photoconductor surface potential when the photoconductor is charged.
[0033] In that case, the absolute value of the development potential applied to the developer carrier must be reduced in order to suppress toner development in non-image areas (so-called image fogging), which can make it difficult to ensure image density in low-temperature, low-humidity environments where the toner charge amount is likely to be high.
[0034] On the other hand, in order to suppress the leakage of electric charge between the protrusions on the developing sleeve surface and the photoconductor surface, it is possible to reduce the absolute value of the development potential applied to the developer carrier. However, in this case, it may be difficult to ensure image density, particularly in a low-temperature, low-humidity environment where the toner tends to have a high charge amount.
[0035] In the present invention, when forming an image, a combination of any one of three types is used: (1) a photoconductor support made of an aluminum alloy having a silicon content within a specific range and a two-component developer, (2) a developing sleeve made of an aluminum alloy having a silicon content within a specific range and a two-component developer, or (3) a photoconductor support made of an aluminum alloy having a silicon content within a specific range, a developing sleeve made of an aluminum alloy having a silicon content within a specific range, and a two-component developer. Furthermore, the resistance value of the carrier contained in the two-component developer is adjusted to within a specific range.
[0036] By adjusting the resistance, the carrier particles release an appropriate amount of charge when the toner and carrier are frictionally charged, preventing excessive charging of the toner. This is believed to result in images with sufficient density, especially in low temperature and low humidity conditions. [Brief description of the drawings]
[0037] [Figure 1] An example of layer structure of an electrophotographic photoreceptor [Diagram 2] An external view of a developer carrier having a developing sleeve [Diagram 3] Cross-sectional view of a developer carrier in which the shaft does not pass through the magnet roller [Figure 4] Cross-sectional view of a developer carrier in which the shaft passes through a magnet roller [Diagram 5] FIG. 1 is a cross-sectional view illustrating an example of a configuration of an image forming apparatus according to the present invention. [Figure 6] An example diagram showing the Vpp value of AC voltage DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0038] The image forming system of the present invention is an image forming apparatus using a two-component developer and at least one of a photoreceptor using an aluminum alloy support or a developer carrier using an aluminum alloy developing sleeve, and the static resistance value of the carrier contained in the two-component developer is 10 8Ω cm or more, 10 12 The electrical conductivity of the photoconductor is in the range of less than Ω·cm, and the silicon content in at least the aluminum alloy forming the support body of the photoconductor or the developing sleeve is in the range of more than 0.6 mass % and not more than 12.6 mass %.
[0039] This feature is a technical feature common to or corresponding to each of the following embodiments (aspects).
[0040] As an embodiment of the present invention, it is preferable from the viewpoint of reducing environmental differences in charging that the carrier comprises carrier particles in which at least the surface of a core particle is coated with a coating resin, and the coating resin has a structure derived from (meth)acrylate.
[0041] From the viewpoint of adjusting the static resistance value of the carrier, it is preferable that the coating resin contains at least one of carbon black, magnesium oxide, and titanium dioxide.
[0042] It is preferable that the exposed area ratio of the core particle on the surface of the carrier particle is within the range of 10.0 to 18.0% of the surface area of the core particle, from the viewpoints of suppressing excessive charging of the carrier particle and suppressing deterioration of the carrier particle.
[0043] From the viewpoint of surface processability of the photoreceptor and developer carrier, it is preferable that the silicon content is in the range of more than 0.8 mass % and not more than 12.6 mass %, based on the total amount of the aluminum alloy forming at least the photoreceptor or the developing sleeve.
[0044] It is preferable that the coating resin has a structure derived from a highly hydrophobic alicyclic (meth)acrylate from the viewpoint of further reducing the environmental difference in electrostatic chargeability.
[0045] The static resistance value of the carrier is 10 8 ~10 10 A value in the range of Ω·cm is preferable from the viewpoint of suppressing a decrease in image density in a low-temperature, low-humidity environment.
[0046] The image forming method of the present invention is an image forming method using a two-component developer and an image forming apparatus equipped with at least one of a photoreceptor using an aluminum alloy support or a developer carrier using an aluminum alloy developing sleeve, wherein the static resistance value of the carrier contained in the two-component developer is 10 8 Ω cm or more, 10 12 The aluminum alloy forming at least the support body of the photoreceptor or the developing sleeve of the developer carrier has a silicon content of more than 0.6 mass % and not more than 12.6 mass %, and can be suitably used in the image forming system of the present invention.
[0047] The present invention, its components, and embodiments for carrying out the present invention will be described in detail below. In this application, the symbol "to" is used to mean that the numerical values before and after the symbol "to" are included as the lower limit and upper limit.
[0048] [Image formation system] The image forming system of the present invention is an image forming apparatus using a two-component developer and at least one of a photoreceptor using an aluminum alloy support or a developer carrier using an aluminum alloy developing sleeve, and the static resistance value of the carrier contained in the two-component developer is 10 8 Ω cm or more, 10 12 The electrical conductivity of the aluminum alloy is in the range of less than Ω·cm, and the silicon content in at least the aluminum alloy forming the support body of the photoreceptor or the developing sleeve of the developer carrier is in the range of more than 0.6 mass % and not more than 12.6 mass %.
[0049] 1. Two-component developer The two-component developer according to the present invention contains a toner for developing an electrostatic image (hereinafter, also simply referred to as "toner") and a carrier, and the static resistance value of the carrier is 10 8 Ω cm or more, 10 12 It is characterized by a resistance of less than Ω·cm.
[0050] In the two-component developer according to the present invention, it is preferable to use a carrier and a toner, which will be described in detail below.
[0051] The amount of toner particles mixed is preferably within a range of 1 to 10% by mass based on the entire two-component developer.
[0052] (1.1) Career One of the main roles of the carrier contained in the two-component developer according to the present invention is to be stirred and mixed with the toner in the developing box and to give the toner a desired charge. Another role of the carrier is to act as an electrode between the developing machine and the photoconductor, and to carry the charged toner to the electrostatic latent image on the photoconductor and to function as a carrier material (i.e., a carrier) to form a toner image.
[0053] The carrier is held on the magnet roller by magnetic force, and after acting on the development, it returns to the development box, where it is stirred and mixed again with new toner, and is used repeatedly for a certain period of time. Therefore, in order to stably maintain the desired image characteristics (image density, fog, white spots, gradation, resolution, etc.), it is naturally required that the characteristics of the carrier are stable throughout the period of use.
[0054] The carrier particles constituting the carrier according to the present invention are preferably core particles, which are metal powders such as iron, ferrite, magnetite, etc., coated with a coating resin, as described below. The carrier particles may contain internal additives such as a resistance adjuster, if necessary.
[0055] (1.1.1) Static resistance The carrier according to the present invention plays a role in transferring the toner onto the photoreceptor, and the static resistance value of the carrier is 10 8 Ω cm or more, 10 12 This makes it possible to suppress the decrease in image density, especially in low-temperature and low-humidity environments, even when the development potential is lowered.
[0056] The static resistance of the carrier is 10 12 If the resistivity is Ωcm or more, the charge transfer in the carrier becomes slow, and as a result, the charge build-up of the toner may be degraded.
[0057] The "charging property of the toner" refers to the property of the toner that indicates how quickly the potential of the toner reaches a desired value when the toner is charged. 8 ~10 10 A resistivity within the range of Ω·cm is preferable because it improves the charge build-up property.
[0058] The static resistance of the carrier is 10 8 If the resistivity is less than Ωcm, the toner may not be sufficiently charged, resulting in image defects such as fogging. This is because if the carrier resistance is too low, the charge tends to leak, resulting in a reduced amount of charge on the toner itself.
[0059] From the above, the static resistance value of the carrier is 10 8 Ω cm or more, 10 12 It is preferable that the resistance is within the range of less than 10 8 ~10 10 It is more preferable that the resistance is in the range of Ω·cm.
[0060] (How to calculate static resistance) The static resistance value of the carrier contained in the two-component developer according to the present invention is calculated as follows: The above "static resistance value" is also called "volume resistivity value".
[0061] First, prepare a two-component developer containing a carrier for which the static resistance value is to be calculated. Then, put the two-component developer into an aqueous solution containing a surfactant, and separate the toner and carrier using ultrasonic waves. After that, use a magnet to extract and separate only the carrier from the two-component developer, and use 1.0 g of the carrier as a sample. Cut the sample into a 1 cm2 cross-sectional area. 2 The insulating cylindrical container is filled with two insulating cylindrical containers, each with a cross-sectional area of 1.0 cm2 at the top and bottom.2 The electrodes are arranged in a rectangular shape.
[0062] Next, measure the thickness t [cm] of the layer formed by the sample under a load of 500 g. After that, apply a DC voltage of 100 V with an insulation resistance meter and read the insulation resistance value R [Ω] at that time.
[0063] In addition, the thickness t [cm] of the layer formed by the sample and the insulation resistance value R [Ω] are substituted into the following formula to calculate the static resistance value.
[0064] (Formula 1) Static resistance value [Ω cm]=R·(S / t) (In the above formula, R [Ω] is the insulation resistance value, S [cm 2 ] is the cross-sectional area of the layer formed by the sample, and t [cm] is the thickness of the layer formed by the sample)
[0065] (1.1.2) Core particles (kinds) The core particles according to the present invention are composed of, for example, iron powder, various ferrites, magnetite, and other metal powders. Among these, ferrite is preferred from the viewpoint of low residual magnetization and favorable magnetic properties. The ferrite preferably contains heavy metals such as copper, zinc, nickel, and manganese, and light metals such as alkali metals and alkaline earth metals.
[0066] Ferrite is a compound represented by the following general formula (1), and the molar ratio y of Fe2O3 constituting the ferrite is preferably within the range of 30 to 95 mol %.
[0067] General formula (1) (MO) x (Fe2O3) y (In the above formula, "M" represents a metal element, "O" represents an oxygen element, "Fe" represents an iron element, and "x" and "y" represent a molar ratio.)
[0068] When the molar ratio y is within the range of 30 to 95 mol %, a desired magnetization is easily obtained, and there is an advantage that the carrier particles are less likely to adhere to each other when the carrier particles are produced.
[0069] Examples of "M" in the general formula (1) include manganese (Mn), magnesium (Mg), strontium (Sr), calcium (Ca), titanium (Ti), copper (Cu), zinc (Zn), nickel (Ni), aluminum (Al), silicon (Si), zirconium (Zr), bismuth (Bi), cobalt (Co), lithium (Li), etc. The above metal elements may be used alone or in combination of two or more.
[0070] From the viewpoint of obtaining low residual magnetization and suitable magnetic properties, manganese, magnesium, strontium, lithium, copper and zinc are preferred, and among them, manganese and magnesium are more preferred. That is, the core particles according to the present invention are preferably ferrite particles containing at least one of manganese and magnesium.
[0071] The core particles may be commercially available products or synthetic products.
[0072] (particle size) The particle size of the core particles is the volume-based median diameter (D 50 The volume-based median diameter (D 50 If the volume-based median diameter (D 50 When the average particle diameter is 13 μm or more, adhesion between carrier particles can be prevented, and excellent image quality with little fogging can be provided.
[0073] The volume-based median diameter of the core particles (D 50 ) can be measured, for example, using a laser diffraction particle size distribution measuring device "HELOS" (manufactured by Sympatique) equipped with a wet disperser, and the saturation magnetization of the core material particles can be measured, for example, using a "DC Magnetization Characteristic Automatic Recorder 3257-35" (manufactured by Yokogawa Electric Corporation).
[0074] (Magnetization) The core particles according to the present invention have a saturation magnetization of 30 to 80 Am 2 / kg, and the residual magnetization is preferably within 5.0 Am 2 By using core particles having such magnetic properties, partial aggregation of the carrier particles is prevented, and the two-component developer is more uniformly dispersed on the surface of the developer transport member, making it possible to form a uniform, finely textured toner image without uneven density.
[0075] (Synthesis method) Examples of methods for synthesizing the core particles include the following methods.
[0076] First, the raw materials are weighed in appropriate amounts, and then pulverized and mixed using a wet media mill, a ball mill, a vibration mill, etc. The time required for pulverization and mixing is preferably 0.5 hours or more, and more preferably within the range of 1 to 20 hours.
[0077] The pulverized material thus obtained is pelletized using a pressure molding machine or the like, and then calcined. The temperature required for the calcination is preferably within the range of 700 to 1200° C., and the time required for the calcination is preferably within the range of 0.5 to 5 hours.
[0078] The obtained pulverized material may be pulverized without using a pressure molding machine, or after pulverization, water may be added to the pulverized material to form a slurry, which may be granulated using a spray dryer and then calcined.
[0079] After the calcination, the mixture is further pulverized using a ball mill or a vibration mill, etc. At this time, water may be added and the mixture may be pulverized using a wet ball mill or a wet vibration mill, etc.
[0080] Thereafter, water and a binder such as polyvinyl alcohol (PVA) are added, and a dispersant is added as necessary to adjust the viscosity, followed by granulation and firing. The firing temperature is preferably within the range of 1000 to 1500° C., and the firing time is preferably within the range of 1 to 24 hours.
[0081] The grinding machine such as the ball mill and the vibration mill is not particularly limited, but in order to effectively and uniformly disperse the raw material, it is preferable to use fine beads having a particle size of 1 cm or less as the media to be used. The degree of grinding can be controlled by adjusting the diameter and composition of the beads to be used and the grinding time.
[0082] The fired product thus obtained is pulverized and classified by a conventional classification method such as air classification, mesh filtration, or sedimentation to adjust the particle size to a desired particle size.
[0083] Thereafter, if necessary, the surface of the pulverized and classified fired product may be subjected to low-temperature heating to perform an oxide coating treatment, and electrical resistance adjustment may be performed. In addition, if necessary, reduction may be performed before the oxide coating treatment, and low magnetic products may be separated by magnetic separation after classification.
[0084] (1.1.3) Coating resin (kinds) The surface of the core particle according to the present invention is preferably coated with a coating resin, and the coating resin preferably has a structure derived from (meth)acrylate from the viewpoint of reducing the environmental difference in charging. In this specification, (meth)acrylic means acrylic or methacrylic.
[0085] Examples of the compound having a structure derived from (meth)acrylate include methacrylic acid ester compounds, acrylic acid ester compounds, and alicyclic (meth)acrylic acid ester compounds.
[0086] Among the above, alicyclic (meth)acrylic acid ester compounds are particularly preferred because they are highly hydrophobic and reduce the amount of moisture adsorbed to the carrier particles in a high-temperature and high-humidity environment, thereby suppressing a decrease in the charge amount.
[0087] Specific examples of methacrylic acid ester compounds include methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isopropyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, n-octyl methacrylate, 2-ethylhexyl methacrylate, stearyl methacrylate, lauryl methacrylate, phenyl methacrylate, benzyl methacrylate, isobornyl methacrylate, diethylaminoethyl methacrylate, and dimethylaminoethyl methacrylate.
[0088] Specific examples of the acrylate ester compounds include methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, isobutyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, stearyl acrylate, lauryl acrylate, phenyl acrylate, and benzyl acrylate.
[0089] Specific examples of alicyclic (meth)acrylic acid ester compounds include isobornyl acrylate, dicyclopentanyl acrylate, cyclohexyl acrylate, methylcyclohexyl acrylate, trimethylcyclohexyl acrylate, t-butylcyclohexyl acrylate, cyclohexylphenyl acrylate, cyclododecyl acrylate, adamantyl acrylate, cyclopentyl methacrylate, cyclohexyl methacrylate, cycloheptyl methacrylate, cyclooctyl methacrylate, etc. Among these, from the viewpoint of environmental stability of the charge amount, etc., those having a cycloalkyl group having 5 to 8 carbon atoms are preferred, and cyclohexyl methacrylate is more preferred.
[0090] As a monomer constituting the coating resin, other monomers than the (meth)acrylic acid ester compound may be used. Examples of the other monomers include, for example, styrene compounds, (meth)acrylic acid, olefin compounds, vinyl halide compounds, vinyl ester compounds, vinyl ether compounds, vinyl ketone compounds, N-vinyl compounds, vinyl compounds, and acrylic acid or methacrylic acid derivatives.
[0091] Specific examples of the styrene compound include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-chlorostyrene, 3,4-dichlorostyrene, p-phenylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, and pn-dodecylstyrene.
[0092] Specific examples of the (meth)acrylic acid include methacrylic acid, acrylic acid, and itaconic acid.
[0093] Specific examples of the olefin compound include ethylene, propylene, and isobutylene.
[0094] Specific examples of the vinyl halide compound include vinyl chloride, vinylidene chloride, vinyl bromide, vinyl fluoride, and vinylidene fluoride.
[0095] Specific examples of the vinyl ester compound include vinyl propionate, vinyl acetate, and vinyl benzoate.
[0096] Specific examples of the vinyl ether compound include vinyl methyl ether and vinyl ethyl ether.
[0097] Specific examples of the vinyl ketone compound include vinyl methyl ketone, vinyl ethyl ketone, and vinyl hexyl ketone.
[0098] Specific examples of the N-vinyl compound include N-vinylcarbazole, N-vinylindole, and N-vinylpyrrolidone.
[0099] Specific examples of the vinyl compound include vinylnaphthalene and vinylpyridine.
[0100] Specific examples of the acrylic acid or methacrylic acid derivative include acrylonitrile, methacrylonitrile, and acrylamide.
[0101] These other monomers may be used alone or in combination of two or more. Among these other monomers, styrene and methacrylic acid are preferred from the viewpoint of the environmental stability of the charge amount.
[0102] The ratio of the structural units derived from the (meth)acrylic acid ester compound to the structural units derived from other monomers in the coating resin is preferably 10:90 to 100:0, and more preferably 30:70 to 70:30.
[0103] (Weight average molecular weight) The weight average molecular weight of the coating resin, i.e., the polymer obtained by polymerizing the monomer, is not particularly limited as long as it is within a range in which the effects of the present invention can be effectively exhibited. The weight average molecular weight is preferably within a range of 200,000 to 800,000, more preferably within a range of 300,000 to 700,000. If the weight average molecular weight is 200,000 or more, it is excellent in that the wear of the resin coating layer formed on the surface of the core particle is not excessively promoted, and adhesion of the carrier particle is unlikely to occur. If the weight average molecular weight is 800,000 or less, it is possible to maintain a good charge amount for a long period of time without causing a decrease in the charge amount due to the migration of the external additive from the toner particle to the surface of the carrier particle.
[0104] The weight average molecular weight is measured by gel permeation chromatography (GPC), and more specifically, the following method may be mentioned.
[0105] The apparatus used was "HLC-8220GPC" (manufactured by Tosoh Corporation) and the column was "TSKguardcolumn SuperHZ-L + TSKgel SuperHZM-M triple series" (manufactured by Tosoh Corporation).
[0106] The column temperature is maintained at 40° C., and tetrahydrofuran (THF) is run as a carrier solvent at a flow rate of 0.35 mL / min.
[0107] The measurement sample is dissolved in tetrahydrofuran at room temperature to a concentration of 1 mg / mL under dissolution conditions of treatment for 10 minutes with a roller stirrer.
[0108] The sample solution is then filtered through a membrane filter with a pore size of 0.2 μm to obtain a sample solution. 10 μL of this sample solution is injected into the device together with the carrier solvent, and detected using a refractive index detector (RI detector).
[0109] The weight-average molecular weight distribution of the measurement sample is calculated using a calibration curve measured using monodisperse polystyrene standard particles. Ten polystyrene samples are used for the calibration curve measurement.
[0110] (Thickness of resin coating layer) The thickness of the resin coating layer is preferably within the range of 0.05 to 4 μm, and more preferably within the range of 0.2 to 3 μm. If the thickness of the resin coating layer is within the above range, the chargeability and durability of the carrier particles can be improved. The thickness of the resin coating layer can be determined by the following method.
[0111] Using a focused ion beam device "SMI2050" (manufactured by Hitachi High-Tech Science Corporation), the carrier particles are cut along a plane passing through the center of the carrier particles to prepare a measurement sample.
[0112] The cross section of the measurement sample is observed at 5000x magnification using a transmission electron microscope "JEM-2010F" (manufactured by JEOL Ltd.). The average value of the maximum and minimum thicknesses in the field of view is then taken as the thickness of the resin coating layer. Five fields of view are measured.
[0113] (Resistance adjuster) The coating resin preferably contains at least one of carbon black, magnesium oxide, and titanium dioxide as a resistance adjusting agent from the viewpoint of adjusting the static resistance value of the carrier coated with the coating resin. Among the above, carbon black is particularly preferred from the viewpoint of its easiness of dispersion in the resin.
[0114] (Exposed area ratio) The charge of the carrier particles is also released through the core particles exposed on the carrier surface. When the exposed area ratio of the core particles is 10% or more, the charge is appropriately released from the carrier particles, and excessive charging of the carrier particles can be suppressed. Also, when the exposed area ratio is 18% or less, the resin covering the carrier particles is not easily peeled off when friction occurs between the carrier particles, and the carrier particles are not easily deteriorated.
[0115] For the reasons mentioned above, it is preferable that the exposed area ratio of the core particle on the surface of the carrier particle is within the range of 10.0 to 18.0% of the surface area of the core particle, from the viewpoint of suppressing excessive charging of the carrier particle and suppressing deterioration of the carrier particle.
[0116] The exposed area ratio of the core particles to the surface of the carrier particle can be measured, for example, by the following method.
[0117] The measurement device used is "K-Alpha" (manufactured by Thermo Fisher Scientific). The main element constituting the coating layer (usually carbon) and the main element constituting the core particle (usually iron) are measured by XPS measurement (X-ray photoelectron spectroscopy measurement).
[0118] At this time, an Al monochromatic X-ray is used as the X-ray source, and the acceleration voltage is set to 7 kV and the emission current is set to 6 mV.
[0119] When the core particles are made of iron oxide, the C1s spectrum is measured for carbon, the Fe2p3 / 2 spectrum is measured for iron, and the O1s spectrum is measured for oxygen.
[0120] The number of carbon, oxygen, and iron elements (represented as "AC," "AO," and "AFe," respectively) are determined, and the iron content of the core particle alone and the iron content of the carrier after the core particle is coated with the coating layer are determined based on the obtained carbon, oxygen, and iron element number ratios in the following formula (2) by substituting them into the following formula.
[0121] (Formula 2) Iron content rate [atomic%]=AFe / (AC+AO+AFe)×100
[0122] The coverage ratio is calculated by substituting the iron content of the core particle alone and the iron content of the carrier after the core particle is covered with the coating layer into the following formula (3).
[0123] (Formula 3) Coverage rate [%] = {1-(iron content of carrier) / (iron content of core particle alone)} x 100
[0124] When a material other than iron oxide is used as the core particle, the coverage can be obtained by measuring the spectrum of the metal elements that make up the core particle in addition to oxygen and performing a similar calculation according to the above formula.
[0125] (Method of producing coating resin) The method for producing the coating resin is not particularly limited, and a conventionally known polymerization method can be appropriately used. For example, a pulverization method, an emulsion dispersion method, a suspension polymerization method, a solution polymerization method, a dispersion polymerization method, an emulsion polymerization method, an emulsion polymerization aggregation method, and other known methods can be used. In particular, from the viewpoint of controlling the particle size, it is preferable to synthesize the resin by the emulsion polymerization method.
[0126] The polymerization initiator, surfactant, and further chain transfer agent used as necessary in the emulsion polymerization method are not particularly limited, and conventionally known ones can be used. Furthermore, the polymerization conditions such as the polymerization temperature are not particularly limited, and conventionally known polymerization conditions can be appropriately used to adjust the polymerization conditions.
[0127] Specifically, it is preferable to carry out emulsion polymerization using various additives described in the Examples below. That is, from the viewpoint of particle size control, it is preferable to carry out emulsion polymerization of the above monomers using sodium dodecyl sulfate as an anionic surfactant, water (ion-exchanged water) as a solvent, and potassium persulfate (KPS) as a polymerization initiator.
[0128] (1.2) Toner for developing electrostatic images (1.2.1) Toner base particles The toner base particles constituting the electrostatic image developing toner contained in the two-component developer according to the present invention contain, for example, a binder resin and, if necessary, a colorant. The toner base particles may further contain other components such as a release agent and a charge control agent, if necessary.
[0129] In the present invention, "toner particles" refers to toner base particles to which an external additive has been added, and an aggregate of toner particles is called "toner". Toner base particles can generally be used as they are as toner particles, but in the present invention, toner base particles to which an external additive has been added are used as toner particles. In the following description, when there is no particular need to distinguish between toner base particles and toner particles, they are also simply referred to as "toner particles". Below, the details of each of the constituent materials of the toner base particles according to the present invention will be described.
[0130] (Binding resin) The binder resin constituting the toner base particles is preferably a thermoplastic resin. As such a binder resin, any resin generally used as a binder resin constituting a toner can be used without any particular limitation.
[0131] Examples of the resin include styrene resin, acrylic resin, styrene-acrylic copolymer resin, polyester, silicone resin, olefin resin, amide resin, epoxy resin, and composite resin in which two or more of these resins are chemically bonded.
[0132] Among these, styrene resin, acrylic resin, styrene-acrylic copolymer resin and polyester are preferred because they have low viscosity and high sharp melting properties. These may be used alone or in combination of two or more kinds.
[0133] In particular, it is preferable to contain a crystalline polyester from the viewpoint of making the toner particles more soluble and achieving energy saving during fixing.
[0134] In this specification, "crystalline" means that the material has a clear endothermic peak, not a stepwise endothermic change, in differential scanning calorimetry. Specifically, the clear endothermic peak means a peak whose half-width is within 15°C when measured at a heating rate of 10°C / min in differential scanning calorimetry (DSC) described in the examples.
[0135] The crystalline polyester has a portion synthesized from a polyvalent carboxylic acid component and a polyhydric alcohol component. The crystalline polyester may be in the form of a composite resin in which the crystalline polyester is chemically bonded to another resin.
[0136] Examples of polyvalent carboxylic acid components include aliphatic dicarboxylic acids such as oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, dodecanedioic acid (1,12-dodecanedicarboxylic acid), 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid.
[0137] Further examples include aromatic dicarboxylic acids such as dibasic acids, such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, malonic acid, and mesaconic acid.
[0138] Further examples include, but are not limited to, their anhydrides and their lower alkyl esters.
[0139] These may be used alone or in combination of two or more.
[0140] Examples of trivalent or higher carboxylic acids include 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, and the like, as well as anhydrides and lower alkyl esters of these.
[0141] These may be used alone or in combination of two or more.
[0142] Furthermore, in addition to the polycarboxylic acid component, a dicarboxylic acid component having a double bond may be used.
[0143] Examples of dicarboxylic acids having a double bond include, but are not limited to, maleic acid, fumaric acid, 3-hexenedioic acid, and 3-octenedioic acid.
[0144] Further, lower esters and acid anhydrides of these compounds are also included.
[0145] On the other hand, as the polyhydric alcohol component, an aliphatic diol is preferable, and a straight-chain aliphatic diol having a main chain portion with 47 to 20 carbon atoms is more preferable.
[0146] When the aliphatic diol is a straight-chain type, the crystallinity of the polyester is maintained and a drop in the melting temperature is suppressed, resulting in excellent toner blocking resistance, image storage stability, and low-temperature fixability.
[0147] Furthermore, when the carbon number is within the range of 4 to 20, the melting point during condensation polymerization with a polyvalent carboxylic acid component is kept low, low-temperature fixing is realized, and the material is easily available for practical use.
[0148] The number of carbon atoms in the main chain portion is more preferably within the range of 4 to 14.
[0149] Examples of aliphatic diols that are preferably used in the synthesis of crystalline polyesters include, but are not limited to, ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, and 1,18-octadecanediol.
[0150] These may be used alone or in combination of two or more.
[0151] Among these, in consideration of availability, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred.
[0152] Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol.
[0153] These may be used alone or in combination of two or more.
[0154] The crystalline polyester may be synthesized by carrying out a polycondensation reaction between a polyvalent carboxylic acid component and a polyhydric alcohol component in the presence of a polymerization catalyst such as dibutyltin oxide or tetrabutoxytitanate according to a conventional method.
[0155] The polycondensation reaction is preferably carried out at a reaction temperature within the range of 180 to 230°C.
[0156] If necessary, the pressure in the reaction system is reduced and the reaction is carried out while removing water and alcohol generated during polycondensation.
[0157] If the monomer is not soluble or compatible at the reaction temperature, a high boiling point solvent may be added as a dissolution aid to dissolve the monomer.
[0158] The polycondensation reaction is carried out while distilling off the solubilizing solvent.
[0159] When a monomer having poor compatibility is present in the copolymerization reaction, it is advisable to condense the monomer having poor compatibility with the acid or alcohol to be polycondensed in advance and then polycondense the monomer with the main component.
[0160] The weight average molecular weight of the crystalline polyester is preferably within the range of 5,000 to 50,000 from the viewpoints of good low-temperature fixability and image storage stability.
[0161] In this specification, the weight average molecular weight of the crystalline polyester is a value measured by GPC, and can be measured under the same measurement conditions as those for the coating resin of the carrier.
[0162] Examples of polymerizable monomers for obtaining binder resins other than crystalline polyesters (hereinafter also referred to as "other resins") include styrene monomers such as styrene, methylstyrene, methoxystyrene, butylstyrene, phenylstyrene, and chlorostyrene.
[0163] Further examples include acrylate monomers such as methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, and n-stearyl acrylate.
[0164] Other examples include methacrylic acid ester monomers such as methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, and 2-ethylhexyl methacrylate. Other examples include carboxylic acid monomers such as acrylic acid, methacrylic acid, and fumaric acid. These polymerizable monomers can be used alone or in combination of two or more.
[0165] These other resins can be produced by known methods such as suspension polymerization, emulsion polymerization, and dispersion polymerization. Among them, emulsion polymerization is preferred from the viewpoint of controlling particle size. When producing other resins by emulsion polymerization, for example, a radical polymerization initiator and a chain transfer agent are used.
[0166] Examples of the radical polymerization initiator include persulfates such as potassium persulfate and ammonium persulfate, water-soluble azo compounds such as 4,4'-azobis(4-cyanovaleric acid) and 2,2'-azobis(2-amidinopropane) hydrochloride, and hydrogen peroxide.
[0167] The above radical polymerization initiators can also be used as redox polymerization initiators if desired, and these can also be used in combination.
[0168] Examples of the combination include a combination of a persulfate and sodium metabisulfite, a combination of sodium sulfite, a combination of hydrogen peroxide and ascorbic acid, and the like.
[0169] Examples of the chain transfer agent include thiol compounds such as n-dodecyl mercaptan, tert-dodecyl mercaptan, and n-octyl mercaptan, as well as halogenated methanes such as tetrabromomethane and tribromochloromethane.
[0170] The weight average molecular weight of the other resin is preferably within the range of 10,000 to 50,000 from the viewpoints of low-temperature fixability and image storage stability.
[0171] The weight average molecular weight of the other resins is a value measured by GPC, and can be measured under the same measurement conditions as those of the coating resin.
[0172] (External additives) For the purpose of controlling the fluidity and chargeability, an external additive is attached to the surface of the toner base particles according to the present invention. As the external additive, conventionally known metal oxide particles can be used.
[0173] Examples of the particles include silica particles, titania particles, alumina particles, zirconia particles, zinc oxide particles, chromium oxide particles, cerium oxide particles, antimony oxide particles, tungsten oxide particles, tin oxide particles, tellurium oxide particles, manganese oxide particles, boron oxide particles, strontium titanate particles, calcium titanate particles, and magnesium titanate particles.
[0174] These may be used alone or in combination of two or more.
[0175] In particular, it is more preferable to use silica particles produced by a sol-gel method, since the silica particles produced by the sol-gel method have a narrow particle size distribution, which is preferable in terms of suppressing variation in adhesion strength.
[0176] The number-average primary particle diameter of the silica particles formed by the sol-gel method is preferably within a range of 55 to 150 nm. The silica particles having a number-average primary particle diameter within this range have a larger particle diameter than other external additives, and therefore act as a spacer. In addition, they have the effect of preventing other external additives having smaller particle diameters from being embedded in the toner base particles when stirred and mixed in the developing machine. They also have the effect of preventing the toner base particles from fusing together.
[0177] The number average primary particle size of metal oxide particles other than silica particles produced by the sol-gel method is preferably within a range of 10 to 70 nm, and more preferably within a range of 10 to 40 nm.
[0178] The number average primary particle size of the metal oxide particles can be measured, for example, by a method of determining the size from an image taken by a scanning electron microscope.
[0179] Furthermore, organic fine particles such as homopolymers of styrene, methyl methacrylate, etc. or copolymers thereof may be used as an external additive, or organic-inorganic composite fine particles obtained by combining the above polymers with inorganic fine particles may be used.
[0180] The metal oxide particles used as the external additive are preferably those whose surfaces have been subjected to a hydrophobic treatment with a known surface treatment agent such as a coupling agent.
[0181] As the above-mentioned surface treatment agent, dimethyldimethoxysilane, hexamethyldisilazane (HMDS), methyltrimethoxysilane, isobutyltrimethoxysilane, decyltrimethoxysilane, and the like are preferable.
[0182] Silicone oil can also be used as the surface treatment agent. Specific examples of silicone oil include organosiloxane oligomers, cyclic compounds such as octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, tetramethylcyclotetrasiloxane, and tetravinyltetramethylcyclotetrasiloxane, and linear or branched organosiloxanes.
[0183] Furthermore, silicone oils having high reactivity and at least modified ends, in which modifying groups have been introduced into the side chain, one end, both ends, one end of the side chain, or both ends of the side chain, may also be used.
[0184] Examples of the modified group include, but are not limited to, an alkoxy group, a carboxyl group, a carbinol group, a higher fatty acid modified group, a phenol group, an epoxy group, a methacryl group, and an amino group.
[0185] In addition, silicone oils having several kinds of modified groups such as amino / alkoxy modified may be used. Dimethyl silicone oil and the modified silicone oils described above, as well as other surface treatment agents, may be used for mixed treatment or combined treatment.
[0186] Examples of the treating agent that can be used in combination include silane coupling agents, titanate coupling agents, aluminate coupling agents, various silicone oils, fatty acids, fatty acid metal salts, esters thereof, and rosin acid.
[0187] In order to further improve the cleaning property and the transfer property, a lubricant can be used as an external additive.
[0188] Specific examples of the lubricant include salts of higher fatty acids such as zinc stearate and calcium stearate, boron nitride, etc. The amount of these external additives added is preferably within a range of 0.1 to 10% by mass, more preferably within a range of 1 to 5% by mass, based on the total mass of the toner particles.
[0189] (Release agent) The toner particles may contain a release agent.
[0190] The release agent is not particularly limited, and examples thereof include known ones such as hydrocarbon waxes such as polyethylene wax, oxidized polyethylene wax, polypropylene wax, oxidized polypropylene wax, and Fischer-Tropsch wax, carnauba wax, fatty acid ester wax, sazol wax, rice wax, candelilla wax, jojoba oil wax, and beeswax wax.
[0191] The content of the release agent in the toner particles is preferably within a range of 1 to 30 parts by mass, and more preferably within a range of 5 to 20 parts by mass, relative to 100 parts by mass of the binder resin.
[0192] (Charge control agent) The toner particles may contain a charge control agent.
[0193] Examples of the charge control agent include metal complexes of salicylic acid derivatives with zinc or aluminum (salicylic acid metal complexes), calixarene compounds, organic boron compounds, and fluorine-containing quaternary ammonium salt compounds.
[0194] The content of the charge control agent in the toner particles is preferably within a range of 0.1 to 5 parts by mass with respect to 100 parts by mass of the binder resin.
[0195] (Coloring agent) The toner particles according to the present invention may further contain a colorant to make it a color toner. Usable colorants include known inorganic or organic colorants. Specific colorants are shown below.
[0196] Examples of black colorants include carbon blacks such as furnace black, channel black, acetylene black, thermal black, and lamp black, and magnetic powders such as magnetite and ferrite.
[0197] Examples of colorants for magenta or red include CI Pigment Red 2, 3, 5, 6, 7, 15, 16, 48:1, 48:2, 48:3, 53:1, 57:1, 60, 63, 64, 68, 81, 83, 87, 88, 89, 90, 112, 114, 122, 123, 139, 144, 149, 150, 163, 166, 170, 177, 178, 184, 202, 206, 207, 209, 222, 238, and 269.
[0198] Examples of colorants for orange or yellow include CI Pigment Orange 31, CI Pigment Orange 43, CI Pigment Yellow 12, 14, 15, 17, 74, 83, 93, 94, 138, 155, 162, 180, and 185.
[0199] Examples of colorants for green or cyan include CI Pigment Blue 2, 3, 15, 15:2, 15:3, 15:4, 16, 17, 60, 62, 66, CI Pigment Green 7, and the like.
[0200] Examples of dyes include CI Solvent Red 1, 49, 52, 58, 63, 111, and 122, CI Solvent Yellow 2, 6, 14, 15, 16, 19, 21, 33, 44, 56, 61, 77, 79, 80, 81, 82, 93, 98, 103, 104, 112, and 162, CI Solvent Blue 25, 36, 60, 70, 93, and 95.
[0201] These colorants may be used alone or in combination of two or more kinds, as required.
[0202] When a colorant is used, the amount added is preferably within a range of 1 to 30% by mass, and more preferably within a range of 2 to 20% by mass, based on the total mass of the toner.
[0203] Colorants that have been surface-modified can also be used.
[0204] As the surface modifier, a conventionally known agent can be used. Specifically, a silane coupling agent, a titanium coupling agent, an aluminum coupling agent, etc. can be preferably used.
[0205] (others) [Volume average particle size] The toner particles according to the present invention have a volume average particle size in the range of 3 to 10 μm. If the volume average particle size is less than 3 μm, the fluidity of the toner particles decreases, and the charge build-up of the toner particles decreases. On the other hand, if it exceeds 10 μm, image quality decreases. The volume average particle size of the toner particles is preferably in the range of 3.5 to 6.5 μm.
[0206] The volume average particle diameter of the toner particles is specifically the volume-based median diameter (D 50 ) shall be adopted.
[0207] The volume-based median diameter of toner particles (D 50 ) can be measured and calculated using a device that connects a computer system for data processing to a Multisizer 3 (manufactured by Beckman Coulter).
[0208] The measurement procedure involves mixing 0.02 g of toner particles with 20 mL of a surfactant solution, and then subjecting the particles to ultrasonic dispersion for 1 minute to prepare a toner particle dispersion.
[0209] The surfactant solution may be, for example, a surfactant solution obtained by diluting a neutral detergent containing a surfactant component ten times with pure water for the purpose of dispersing toner particles.
[0210] This toner particle dispersion is pipetted into a beaker containing an ISOTON II (manufactured by Beckman Coulter) in a sample stand until the measurement concentration falls within the range of 5 to 10%, and the measurement is performed by setting the measurement count to 25,000 particles.
[0211] The aperture diameter of the Multisizer 3 used is 100 μm.
[0212] The measurement range of 1 to 30 μm was divided into 256 parts to calculate the frequency, and the particle size of 50% of the largest volume fraction was determined as the volume-based median diameter (D 50 )
[0213] The volume average particle size of the toner particles can be controlled by controlling the concentration of the coagulant, the amount of the organic solvent added, or the fusion time in the above-mentioned production method.
[0214] [Average circularity] The average circularity of the toner particles according to the present invention is preferably 0.98 or less, and more preferably 0.930 to 0.975.
[0215] If the average circularity falls within this range, the toner particles will be more easily charged.
[0216] The average circularity can be measured, for example, by using a flow type particle image analyzer "FPIA-3000" (manufactured by Sysmex Corporation), and specifically, it can be measured by the following method.
[0217] The toner particles are wetted with an aqueous surfactant solution, ultrasonically dispersed for 1 minute, and then measured using the "FPIA-3000" under the measurement conditions of HPF (high magnification imaging) mode at an appropriate concentration of 3,000 to 10,000 HPF detections. Within this range, reproducible measurements can be obtained. The circularity is calculated using the following formula (5).
[0218] Equation (5) Circularity = (perimeter of a circle with the same projected area as the particle image) / (perimeter of the particle projected image)
[0219] The average circularity is the arithmetic mean value obtained by adding up the circularity of each particle and dividing the sum by the total number of particles measured.
[0220] The average circularity of the toner particles can be controlled by controlling the temperature, time, etc. during the aging treatment in the above-mentioned production method.
[0221] (1.2.2) Toner manufacturing method The toner base particles according to the present invention, that is, the particles at the stage before the addition of external additives, can be produced by a known toner production method.
[0222] That is, there are a so-called pulverization method in which toner base particles are produced through kneading, pulverization, and classification processes, and a so-called polymerization method in which a polymerizable monomer is polymerized and particles are formed while controlling the shape and size at the same time.
[0223] Toner particles are produced by adding external additives to toner base particles and mixing them.
[0224] As a mixer for the external additives, various known mixers such as a Turbula mixer, a Henschel mixer, a Nauta mixer, and a V-type mixer can be used.
[0225] For example, when a Henschel mixer is used, the peripheral speed of the tip of the stirring blade is preferably within a range of 30 to 80 m / s, and the mixture is stirred and mixed within a range of 20 to 50° C. for about 10 to 30 minutes.
[0226] 2.Photoreceptor A "photoreceptor" is an object that carries a latent or visible image on its surface in an electrophotographic image forming method. The photoreceptor according to the present invention is composed of, for example, a support, a photosensitive layer, a protective layer, and other layers. Figure 1 shows an example of the layer structure of the electrophotographic photoreceptor according to the present invention.
[0227] In image formation, the surface of the photoconductor is first charged to create a potential difference between it and the support surface. Next, an exposure device generates charges from the photosensitive layer, which cancel out the charges on the photoconductor surface, forming an electrostatic latent image on the photoconductor surface. Next, a development bias voltage is applied to the developer carrier, which electrostatically attracts toner from the developer carrier to the latent image area on the photoconductor surface, developing it.
[0228] Here, if there are convex portions of a certain size or larger on the surface of the photoreceptor, the electric field tends to concentrate on the convex portions, and charge leakage occurs between the support surface and the outermost surface of the photoreceptor when the outermost surface of the photoreceptor is charged.
[0229] The absolute value of the potential becomes low at the location on the surface of the photoconductor where the charge has leaked, and as a result, toner is more likely to be attracted to the location where the charge has leaked.
[0230] When the toner is transferred and fixed to a recording medium, the areas to which the toner is easily attracted become image defects known as "black spots."
[0231] In order to suppress leakage of electric charges on the surface of the photoconductor according to the present invention, it is effective to set the absolute value of the potential difference between the outermost surface of the photoconductor and the support to a small value.
[0232] However, if the absolute value of the potential difference is set small, the toner is attracted to the non-image area on the outermost surface of the photoconductor, causing so-called image fogging.
[0233] Here, the "non-image portion" refers to a portion of the recording medium on which an image is not originally to be formed.
[0234] Moreover, "image fogging" refers to a toner image being formed in a non-image area.
[0235] In order to prevent such image fog, it is effective to set the absolute value of the voltage applied during development to a small value, but in this case, the toner becomes difficult to separate from the photoconductor, and the image density may decrease, especially in a low-temperature, low-humidity environment where the toner charge amount is likely to increase.
[0236] However, the static resistance is 10 8 ~10 12 By using the above-mentioned carrier within the range of Ωcm in the two-component developer, it is possible to prevent the charge amount of the toner from increasing, and to suppress the above-mentioned decrease in image density.
[0237] (2.1) Support The support of the photoreceptor according to the present invention is an electrically conductive support made of an aluminum alloy.
[0238] (Silicon content) The silicon content in the aluminum alloy is in the range of more than 0.6 mass % and not more than 12.6 mass %.
[0239] The aluminum alloy may contain elements other than silicon, such as copper, chromium, nickel, and zinc.
[0240] If the silicon content in the aluminum alloy is 0.6% by mass or less, the surface of the photoconductor becomes uneven due to poor workability, and if the silicon content in the aluminum alloy exceeds 12.6% by mass, coarse crystals (protrusions) due to the eutectic of silicon and aluminum are likely to occur, which can easily cause image defects such as black spots.
[0241] From the viewpoint of the processability of the surface of the support of the photoreceptor, the silicon content in the aluminum alloy is more preferably more than 0.8 mass %.
[0242] [Measurement method] The silicon content in the aluminum alloy is obtained by measuring the amount of the elemental silicon, and the amount of the elemental silicon can be measured, for example, by inductively coupled plasma optical emission spectrometry.
[0243] Inductively coupled plasma optical emission spectrometry is a method in which a solution sample in which metals are dissolved in an acid or alkali is sprayed into Ar plasma, the excited light is separated into individual wavelengths, and the type and content of elements are quantified from the light intensity.
[0244] With this method, there is a linear relationship between light intensity and content from trace to high concentrations, making it possible to analyze each element simultaneously.
[0245] As a measuring device for high frequency inductively coupled plasma optical emission spectrometry, for example, "ULTIMA2000 (manufactured by Horiba, Ltd.)" can be used.
[0246] In addition, an optical emission spectrometer with an argon atmosphere discharge emission stand, an optical emission spectrometer with an atmospheric discharge emission stand, a glow discharge mass spectrometer (GD-MS), an X-ray fluorescence spectrometer (XRF), etc. can also be used.
[0247] When a coating layer such as a resin layer is present on the support of the photoreceptor according to the present invention, the measurement is carried out after the coating layer such as the resin layer is appropriately removed with a solvent or the like.
[0248] (2.2) Photosensitive layer The photosensitive layer is a layer for forming an electrostatic latent image of a desired image on the surface of the photoreceptor by an exposure means described later. The photosensitive layer may be a single layer or may be composed of a plurality of laminated layers. Preferred examples of the photosensitive layer include a single layer containing a charge transport material and a charge generating material, and a laminate of a charge transport layer containing a charge transport material and a charge generating layer containing a charge generating material.
[0249] (2.3) Protective layer The protective layer is a layer for improving the mechanical strength of the photoreceptor surface and improving scratch resistance and abrasion resistance. A preferred example of the protective layer is a layer containing a polymerized and cured product of a composition containing a polymerizable monomer.
[0250] (2.4) Other layers The photoreceptor may further include layers other than the above-mentioned conductive support, photosensitive layer, and protective layer.
[0251] (2.4.1) Middle Tier Preferred examples of the other layers include an intermediate layer.
[0252] The intermediate layer is, for example, a layer having a barrier function and an adhesive function, which is disposed between the conductive support and the photosensitive layer.
[0253] (2.4.2) Outermost layer In this specification, the outermost layer of the photoreceptor refers to a layer disposed on the outermost side that comes into contact with the toner. The outermost layer is not particularly limited, but is preferably the above-mentioned protective layer.
[0254] In the photoreceptor according to the present invention, the outermost layer preferably contains inorganic particles, and more preferably the inorganic particles are surface-treated with a surface treatment agent such as a silane coupling agent, an electron transporting compound, or a compound having a polymerizable functional group.
[0255] (Inorganic particles) The inorganic particles are not particularly limited, but examples thereof include titanium oxide, zinc oxide, alumina (aluminum oxide), silica (silicon oxide), tin oxide, antimony oxide, indium oxide, bismuth oxide, magnesium oxide, lead oxide, tantalum oxide, yttrium oxide, cobalt oxide, copper oxide, manganese oxide, selenium oxide, iron oxide, zirconium oxide, germanium oxide, niobium oxide, molybdenum oxide, vanadium oxide, tin-doped indium oxide, antimony-doped tin oxide and zirconium oxide, and copper aluminum composite oxide (CuAlO2).
[0256] The inorganic particles preferably contain at least one of tin, zinc, titanium, silicon and copper, more preferably contain at least one of tin, zinc, titanium and copper, and particularly preferably contain at least one of tin, zinc and copper.
[0257] The number average primary particle size of the inorganic particles is not particularly limited, but is preferably within the range of 5 to 300 nm, and more preferably within the range of 10 to 200 nm.
[0258] The number average primary particle size of the inorganic particles can be calculated from the average length of the major axis of particle images observed under a scanning electron microscope.
[0259] (Binding resin) The outermost layer (protective layer) may contain a binder resin.
[0260] The binder resin for the outermost layer may be a known binder resin, which may be used alone or in combination of two or more kinds.
[0261] (2.5) Photoreceptor manufacturing method The photoreceptor according to the present invention can be manufactured by a known method for manufacturing an electrophotographic photoreceptor. It is preferable to manufacture the photoreceptor by a method including a step of applying an outermost layer forming coating liquid containing inorganic particles to the surface of a photosensitive layer formed on an aluminum alloy support, and a step of irradiating the applied outermost layer forming coating liquid with active energy rays or heating the applied outermost layer forming coating liquid to obtain a cured product of the outermost layer forming composition.
[0262] (others) The thickness of the outermost layer is preferably within the range of 1 to 10 μm, and more preferably within the range of 1.5 to 5 μm.
[0263] 3. Developer carrier The silicon content in the aluminum alloy forming the developing sleeve in the developer carrier according to the present invention is in the range of more than 0.6 mass % and not more than 12.6 mass %.
[0264] Here, if there are protrusions of a certain size or more on the surface of the developer carrier, charge leakage occurs between the protrusions and the surface of the photoconductor when a toner image is formed on a recording medium.
[0265] When such charge leakage occurs, the absolute value of the potential on the surface of the photoconductor becomes smaller in certain parts, which makes it easier for toner to be attracted to the parts where the charge has leaked.
[0266] When the toner is transferred and fixed to a recording medium, the areas to which the toner is easily attracted become image defects known as "black spots."
[0267] In order to suppress leakage of electric charges from the surface of the developer carrying member according to the present invention, it is necessary to set the absolute value of the potential when the developing bias voltage is applied small.
[0268] However, if the absolute value of the potential when the developing bias voltage is applied is set small, the toner becomes difficult to separate from the photoconductor, which can result in a decrease in image density, particularly in low-temperature, low-humidity environments where the toner charge amount is likely to be high.
[0269] However, the static resistance is 10 8 ~10 12 By using the above-mentioned carrier within the range of Ωcm in the two-component developer, it is possible to prevent the charge amount of the toner from increasing, and to suppress the above-mentioned decrease in image density.
[0270] (Configuration of Developer Carrier) The developer carrying member according to the present invention is composed of, for example, a developing sleeve, a flange, a shaft and a magnet roller.
[0271] The above-mentioned "developing sleeve" refers to a means having a function of carrying an appropriately charged developer and supplying the developer to a photoconductor on which an electrostatic latent image is formed, and is, for example, a part of a developer carrier of a developing device provided in an electrophotographic image forming apparatus.
[0272] Further, the above-mentioned developing sleeve does not include a tube-like developing sleeve having lotus-root-shaped holes in cross section, rather than a simple cylindrical shape as in JP-A-2003-91084.
[0273] FIG. 2 is an external view of the developer carrier.
[0274] For example, the developing sleeve 11 in FIG. 2 is rotatable and cylindrical, and serves to carry and transport the developer on its surface.
[0275] The surface of the developing sleeve 11 is not limited to the configuration shown in FIG. 2, and for example, grooves or the like may be formed on the surface.
[0276] 3 and 4 are examples of axial cross-sectional views of the developer carrier of the present invention, each of which has a magnet roller and a shaft having different shapes.
[0277] The developer carrier according to the present invention does not need to include a magnet portion such as a magnet roller as part of its configuration, and is not limited to the configurations shown in FIGS.
[0278] FIG. 3 is a cross-sectional view of a developer carrier having a structure in which the shaft does not pass through the magnet roller.
[0279] As shown in FIG. 3, the developer carrier 10 has a shaft 16 fixed by inserting the shaft into a hole formed in the magnet roller 12, and is provided with a developing sleeve 11 made of a non-magnetic material on the outer periphery of the magnet roller 12.
[0280] FIG. 4 is a cross-sectional view of a developer carrier having a shaft passing through a magnet roller.
[0281] As shown in FIG. 4, the developer carrier 10 has a magnet roller 12 fixed around a shaft 16, and a developing sleeve 11 made of a non-magnetic material attached to the outer periphery of the magnet roller 12.
[0282] The developing sleeve 11 is connected to the magnet roller 12 with a predetermined gap therebetween via a bearing portion 17 such as a bearing provided on the outside of the magnet roller 12 .
[0283] On the outer side of the bearing portion 17 in the axial direction of the developing sleeve 11 , a non-driving side flange 18 and a driving side flange 19 are connected to the developing sleeve 11 .
[0284] Incidentally, the non-driving side flange 18 and the driving side flange 19 may be reversed, and the present invention is not limited to this.
[0285] The anti-driving side flange 18 and the driving side flange 19 are held relative to the developing container and are rotated together with the developing sleeve 11 .
[0286] (Silicon content) The silicon content in the aluminum alloy forming the developing sleeve according to the present invention is in the range of more than 0.6% by mass and not more than 12.6% by mass. If the silicon content in the aluminum alloy is 0.6% by mass or less, the workability is reduced, so that the surface of the developer carrier becomes uneven, and unevenness occurs in the image. If the silicon content in the aluminum alloy is more than 12.6% by mass, the strength increases, but coarse crystals (protrusions) due to the eutectic of silicon and aluminum are likely to occur. Therefore, charge leakage between the photoconductor and the photoconductor is likely to occur, resulting in black spots.
[0287] From the viewpoint of the workability of the surface of the developing sleeve according to the present invention, the silicon content in the aluminum alloy is more preferably more than 0.8 mass %.
[0288] [Measurement method] The method for measuring the silicon content in the aluminum alloy is the same as the method for measuring the silicon content in the aluminum alloy in the support of the photoreceptor described above.
[0289] (surface) From the viewpoint of imparting an appropriate roughness to the surface of the developing sleeve of the developer carrier, sandblasting is preferred, which makes it possible to maintain the outer peripheral surface of the developing sleeve at an appropriate roughness.
[0290] 4.Image forming method The image forming method of the present invention is an image forming method using a two-component developer and an image forming apparatus equipped with at least one of a photoreceptor using an aluminum alloy support or a developer carrier using an aluminum alloy developing sleeve, wherein the static resistance value of the carrier contained in the two-component developer is 10 8 ~10 12 The aluminum alloy forming at least the support body of the photoreceptor or the developing sleeve of the developer carrier has a silicon content of more than 0.6 mass % and not more than 12.6 mass %, and can be suitably used in the image forming system of the present invention.
[0291] 5. Image forming equipment In the image forming method of the present invention, for example, the following image forming apparatus can be used, which includes a charging unit, an exposure unit, a developing unit, and a transfer unit. The image forming apparatus also includes either or both of the above-mentioned photoconductor and developer carrier.
[0292] Fig. 5 is an explanatory cross-sectional view showing an example of the configuration of an image forming apparatus according to the present invention. The image forming apparatus 100 shown in Fig. 5 is called a tandem type color image forming apparatus, and has four image forming units 110Y, 110M, 110C, and 110Bk, a paper feed conveying means 150, and a fixing means 170.
[0293] An original image reading device SC is disposed on the upper portion of the main body of the image forming apparatus 100.
[0294] The image forming units 110Y, 110M, 110C, and 110Bk are arranged side by side in the vertical direction.
[0295] The image forming units 110Y, 110M, 110C, and 110Bk each include a rotating drum-shaped photoconductor 111Y, 111M, 111C, and 111Bk, charging means 113Y, 113M, 113C, and 113Bk, exposure means 115Y, 115M, 115C, and 115Bk, developing means 117Y, 117M, 117C, and 117Bk, primary transfer rollers (primary transfer means) 133Y, 133M, 133C, and 133Bk, and cleaning means 119Y, 119M, 119C, and 119Bk, which are arranged sequentially in the rotational direction of the photoconductor in the outer circumferential surface area.
[0296] The photoreceptor uses an aluminum alloy support, and the silicon content in the aluminum alloy is in the range of more than 0.6 mass % and not more than 12.6 mass %.
[0297] A configuration is adopted in which toner images of yellow (Y), magenta (M), cyan (C) and black (Bk) are formed on the photoconductors 111Y, 111M, 111C and 111Bk, respectively.
[0298] In the following description, the image forming unit 110Y will be taken as an example when referring to the drawings.
[0299] <Charging means> The charging means is a means for uniformly charging the surface of the photoreceptor.
[0300] Charging means include contact types such as charging rollers, charging brushes, and charging blades, and non-contact types such as corona chargers (corotron chargers, strocotton chargers, etc.). Contact types have the advantage of generating less harmful ozone gas during the charging process. Non-contact types have the advantage of being less prone to filming than contact types because they are not close-proximity discharges.
[0301] The charging means provided in the image forming system of the present invention may be of a contact type or a non-contact type.
[0302] It is preferable that the charging means is a proximity charging roller or a contact charging roller, since this reduces the amount of harmful ozone gas generated during the charging process and is advantageous for achieving high image quality and miniaturization of the apparatus.
[0303] 5 is of a contact type. The charging unit 113Y in this example is made up of a charging roller arranged in contact with the surface of the photoconductor 111Y, and a power source that applies a voltage to the charging roller.
[0304] <Exposure means> The exposure unit is a unit that exposes the photoconductor, to which a uniform potential has been applied by the charging unit, based on an image signal, to form an electrostatic latent image corresponding to the image.
[0305] Examples of the exposure means include a means consisting of an LED in which light emitting elements are arranged in an array in the axial direction of the photoconductor, and an imaging element, and a laser optical system.
[0306] <Developing method> The developing means (developing machine) is a means for supplying a developer to the surface of the photoconductor, developing the electrostatic latent image formed on the surface of the photoconductor, and forming a toner image.
[0307] The developer used herein is one containing the toner and carrier described above. In addition, the static resistance of the carrier is 10 8 Ω cm or more, 10 12 It is in the range of less than Ω·cm.
[0308] The developing means may be equipped with a lubricant supplying means for supplying a lubricant to the developer, and it is preferable from the viewpoint of improving abrasion resistance that the developer supplied by the developing means contains a lubricant.
[0309] From the viewpoint of improving abrasion resistance, it is more preferable that the lubricant is a metal soap.
[0310] The developing means 117Y shown in FIG. 5 is specifically composed of a developer carrier 118Y that incorporates a magnet roller and rotates while holding a developer, and a voltage application device (not shown) that applies a DC and / or AC bias voltage between the photoconductor 111Y and the developer carrier 118Y.
[0311] As described above, the developer carrying member is composed of the developing sleeve, the flange, the shaft and the magnet roller.
[0312] The aluminum alloy of the developing sleeve has a silicon content of more than 0.6 mass % and not more than 12.6 mass %.
[0313] The developer is transported to the photoconductor 111Y by the rotation of the developer carrier 118Y. Then, a thin layer of toner on the developer carrier 118Y comes into contact with the photoconductor 111Y to develop the electrostatic latent image on the photoconductor 111Y.
[0314] The developer carrier 118Y is connected to a voltage application device. This voltage application device applies a DC and / or AC bias voltage to the developer carrier 118Y. The developer carrier 118Y is configured to be able to adjust the development bias to a desired value by controlling the voltage applied to the developer carrier 118Y.
[0315] Due to a potential difference (development potential difference) between the potential of the electrostatic latent image carried by the developer carrier 118Y and the photoconductor 111Y, an electric field is formed in a development section where the developer carrier 118Y and the photoconductor 111Y face each other.
[0316] The toner in the developer transported to the developing section by the rotation of the developer carrier 118Y moves due to the force exerted by the electric field, and is attracted to the electrostatic latent image on the photoconductor 111Y.
[0317] The electrostatic latent image carried on the photoconductor 111Y is visualized, so that a toner image corresponding to the shape of the electrostatic latent image is formed on the surface of the photoconductor 111Y.
[0318] [Development Potential Difference] The "development potential difference" is the difference between the potential (Vi) of the image area and the development potential (Vdc). From the viewpoint of both ensuring image density and suppressing fogging, the absolute value of the development potential difference is preferably within a range of 200 to 600V, and more preferably within a range of 300 to 400V.
[0319] <Transfer Method> The transfer means is a means for transferring a toner image onto a recording medium. Examples of the transfer means include a corona transfer device using corona discharge, a transfer belt, a transfer roller, etc. When an intermediate transfer body is used, the primary transfer roller serves as the transfer means.
[0320] 5 transfers the toner image formed on the photoconductor 111Y onto the endless belt-like intermediate transfer body 131. The primary transfer roller 133Y is disposed in contact with the intermediate transfer body 131.
[0321] In the image forming apparatus 100 shown in FIG. 5, an intermediate transfer method is adopted in which the toner images formed on the photoconductors 111Y, 111M, 111C, and 111Bk are transferred to the intermediate transfer body 131 by primary transfer rollers (primary transfer means) 133Y, 133M, 133C, and 133Bk, and each toner image transferred to the intermediate transfer body 131 is transferred to the transfer material P by a secondary transfer roller (secondary transfer means) 217, but a direct transfer method may also be adopted in which the toner images formed on the photoconductors are transferred directly to the transfer material P by a transfer means. EXAMPLES
[0322] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the examples, the terms "parts" and "%" are used, but they represent "parts by mass" or "% by mass" unless otherwise specified.
[0323] A. Preparation of each photoreceptor (A.1) Preparation of photoreceptor 1 Photoreceptor 1 was prepared according to the following procedure.
[0324] (Preparation of conductive support) A conductive support made of an aluminum alloy was prepared. The silicon content relative to the total amount of the aluminum alloy is 0.7 mass %. The conductive support has an outer diameter of 30 mm and a length of 360 mm.
[0325] (Formation of the intermediate layer) Next, the following component [1] was dispersed in the amounts shown below to prepare a coating liquid for forming an intermediate layer.
[0326] <Ingredient [1]> Polyamide resin 1.0 parts by weight Titanium oxide 1.1 parts by mass Ethanol 15 parts by weight
[0327] At this time, a sand mill was used as the dispersing machine for component (1), and dispersion was carried out for 10 hours in a batch manner.
[0328] The polyamide resin of the above component [1] used as the binder resin is "X1010" (manufactured by Daicel Degussa Corporation).
[0329] The titanium oxide of component [1] used as the conductive particles is "SMT500SAS" (manufactured by Teika Corporation), and the number average primary particle size is 0.035 μm.
[0330] A coating solution for forming an intermediate layer, prepared by dispersing component [1], was applied to the outer peripheral surface of the conductive support by a dip coating method, and the coating solution was dried in an oven at 110° C. for 20 minutes.
[0331] As a result, an intermediate layer having a thickness of 2 μm was formed on the surface of the conductive support.
[0332] (Formation of Charge Generation Layer) Next, the following component [2] was mixed in the amounts shown below to prepare a coating solution for the charge generating layer.
[0333] <Ingredient [2]> Mixed crystal of adduct A and charge generating substance 24 parts by mass Polyvinyl butyral resin 12 parts by weight Mixed liquid A 400 parts by mass
[0334] The charge generating substance of the above component [2] is titanyl phthalocyanine which has clear peaks at 8.3°, 24.7°, 25.1°, and 26.5° in Cu-Kα characteristic X-ray diffraction spectrum measurement.
[0335] The adduct A of component [2] is a compound in which (2R,3R)-2,3-butanediol is added to the charge generating substance (the above titanyl phthalocyanine) in a 1:1 ratio.
[0336] The polyvinyl butyral of the above component [2] is "S-LEC BL-1" (manufactured by Sekisui Chemical Co., Ltd.) ("S-LEC" is a registered trademark of the company).
[0337] Mixture A of component [2] is 3-methyl-2-butanone / cyclohexanone = 4 / 1 (V / V).
[0338] At this time, the mixer for component [2] was a circulation type ultrasonic homogenizer "RUS-600TCVP" (manufactured by Nippon Seiki Seisakusho Co., Ltd.) under the following conditions.
[0339] <Condition> The vibration frequency of the circulating ultrasonic homogenizer is 19.5 kHz, the output is 600 W, and the circulation flow rate is 40 L per hour, and dispersion is performed for 0.5 hours.
[0340] A coating solution for the charge generating layer prepared by mixing component [2] was applied to the surface of the intermediate layer by dip coating, and the coating solution was dried in an oven at 120° C. for 1 hour.
[0341] As a result, a charge generating layer having a thickness of 0.3 μm was formed on the surface of the intermediate layer.
[0342] (Formation of charge transport layer) The following components [3] were mixed in the amounts shown below and dissolved to prepare a coating solution [A1] for the charge transport layer.
[0343] <Ingredient [3]> Charge transport material CTM-1 75 parts by mass Polycarbonate 100 parts by weight Antioxidant 4 parts by weight
[0344] The chemical structure of the charge transport material CTM-1 of the above component [3] is shown below.
[0345] [ka]
[0346] The polycarbonate of the above component [3] is “Z300” (manufactured by Mitsubishi Gas Chemical Company, Inc.).
[0347] The antioxidant of the above component [3] is “IRGANOX1010” (manufactured by BASF) (“IRGANOX” is a registered trademark of the company).
[0348] The coating solution [A1] for the charge transport layer of the charge generating layer was applied and dried at 120° C. for 70 minutes.
[0349] As a result, a charge transport layer having a thickness of 21 μm was formed on the surface of the charge generation layer.
[0350] (A.2) Preparation of photoreceptors 2 to 5 Photoreceptors 2 to 5 were prepared in the same manner as in the preparation of photoreceptor 1, except that the content of silicon relative to the total amount of aluminum alloy was set to the amount shown in Table I.
[0351] [Table 1]
[0352] B. Preparation of the developer carrier (B.1) Preparation of developer carrier 1 The developer carrying member 1 was prepared according to the following procedure.
[0353] (Making of developing sleeve) [Preparation of Support] A cylindrical support made of an aluminum alloy was prepared.
[0354] The silicon content in the aluminum alloy of the cylindrical support is 0.5 mass %.
[0355] The cylindrical support is a thin-walled cylindrical support having an outer diameter of 16 mm, an inner diameter of 15 mm, and a wall thickness of 1 mm.
[0356] [Sandblasting] The developer carrying member was sandblasted on the outer peripheral surface of the cylinder by spraying glass beads with a blast gun, to prepare a developing sleeve. The roughness (Rz) of the sleeve surface was 10 μm.
[0357] The processing conditions for the sandblasting treatment are as follows:
[0358] <Processing conditions> Glass bead type: FGB#80 Glass beads feed rate: 200g / min Distance from blast gun to cylinder: 100mm Blast gun movement speed: 5.0cm / sec Compressed air pressure: 0.23MPa Cylinder rotation speed: 545 rpm
[0359] (Installation of magnetic rollers) A magnet roller was disposed inside the above-mentioned developing sleeve as shown in FIG.
[0360] (B.2) Preparation of Developer Carriers 2 to 5 Developer carriers 2 to 5 were prepared in the same manner as in the preparation of developer carrier 1, except that the silicon content in the aluminum alloy used for the developing sleeve was set to the amount shown in Table II.
[0361] [Table 2]
[0362] C. Preparation of the Carrier (C.1) Preparation of coating resin (C.1.1) Preparation of coating resin 1 To an aqueous solution of 0.3 mass % sodium benzenesulfonate, monomers of cyclohexyl methacrylate and styrene were added in a mass ratio of (50:50).
[0363] A coating resin 1 was prepared by adding potassium peroxodisulfate in an amount equivalent to 0.5% by mass of the total amount of the above monomers and carrying out emulsion polymerization.
[0364] The weight average molecular weight of the above-mentioned coating resin 1 was measured using a known measuring device and found to be 500,000.
[0365] (C.1.2) Preparation of coating resins 2 to 5 Coating resins 2 to 5 were prepared in the same manner as for coating resin 1, except that the coating layer material was changed as shown in Table III.
[0366] [Table 3]
[0367] (C.1) Preparation of Carrier 1 Carrier 1 was prepared according to the following procedure.
[0368] (Preparation of core particles) The volume average particle size is 35 μm and the saturation magnetization is 61 A m 2 / kg of Mn-Mg-Sr-based "ferrite particles" were prepared.
[0369] The volume resistivity of the above ferrite particles is 4.5×10 7 It was Ωcm.
[0370] (Coating of core particles) 100 parts by mass of the "core particles" prepared above and 3.55 parts by mass of "coating resin 1" were added to a high-speed mixer equipped with a stirring blade.
[0371] At this time, the mixture was mixed and stirred for 15 minutes at 22° C. under conditions where the peripheral speed of the horizontal rotor was 8 m / sec.
[0372] Thereafter, the mixture was mixed at 120° C. for 50 minutes to produce Carrier 1 having a resin coating layer on the surface of the core particles by the action of mechanical impact force (mechanochemical method).
[0373] The exposed core area ratio of carrier 1 is 19%, and the volume resistance is 10 8 The value was Ω·cm.
[0374] (C.2) Preparation of carriers 2 to 7 and 11 to 14 Carriers 2 to 7 and 11 to 14 were prepared in the same manner as in the preparation of Carrier 1, except that the type and amount of the coating resin were changed as shown in Table IV.
[0375] (C.3) Preparation of Carrier 8 100 parts by mass of the "core particles" prepared above and 3.75 parts by mass of "coating resin 1" were added to a high-speed mixer equipped with a stirring blade.
[0376] At this time, carbon black with a particle size of 25 nm (volume resistivity: 1.2 × 10 -1 0.5 parts by mass of CrN2O3 (ohm·cm) was added and mixed at 22°C for 15 minutes with a horizontal rotor blade peripheral speed of 8 m / sec.
[0377] Thereafter, the mixture was mixed at 120° C. for 50 minutes to produce a carrier 8 having a resin coating layer on the surface of the core particles by the action of mechanical impact force (mechanochemical method).
[0378] The exposed core area ratio of carrier 8 is 13%, and the volume resistance is 10 9 The value was Ω·cm.
[0379] (C.4) Preparation of Carriers 9 and 10 Carriers 9 and 10 were prepared in the same manner as in the preparation of Carrier 8, except that the resistance adjuster was changed as shown in Table IV.
[0380] [Table 4]
[0381] D. Toner Preparation Only one type of toner was produced, and this toner was designated as Toner 1.
[0382] (D.1) Preparation of amorphous polyester particle dispersion (a1) (D.1.1) Preparation of amorphous polyester (A1) Into a reaction vessel equipped with a stirrer, a thermometer, a condenser, and a nitrogen gas inlet tube, the following monomer [1] and 0.25 parts by mass of "tin dioctylate" per 100 parts by mass of the total of the following monomer [1] were added.
[0383] <Monomer [1]> Bisphenol A ethylene oxide 2.2 mole adduct 40 mole parts Bisphenol A propylene oxide 2.2 mole adduct 60 mole parts Dimethyl terephthalate 60 parts by mole Dodecenyl succinic anhydride 20 mole parts
[0384] The reaction was carried out in a reaction vessel at 235° C. for 6 hours under a nitrogen gas flow.
[0385] Thereafter, the temperature inside the reaction vessel was lowered to 200° C., and 15 parts by mole of dimethyl fumarate and 5 parts by mole of trimellitic anhydride were added to the reaction vessel, and the mixture was reacted in the reaction vessel for 1 hour.
[0386] The temperature inside the reaction vessel was raised to 220° C. over 5 hours, and polymerization was carried out under a pressure of 10 kPa until a desired molecular weight was reached, producing a pale yellow, transparent amorphous polyester (A1).
[0387] The amorphous polyester (A1) had a weight average molecular weight (Mw) of 35,000, a number average molecular weight (Mn) of 8,000, and a glass transition temperature (Tg) of 56°C.
[0388] (D.1.2) Preparation of amorphous polyester (A1) particle dispersion Next, the amorphous polyester (A1) and the following mixed solution [2] were placed in a separable flask in the amounts shown below, and thoroughly mixed to dissolve.
[0389] Amorphous polyester (A1) 200.0 parts by mass
[0390] <Mixed solution [2]> Methyl ethyl ketone 100.0 parts by mass Isopropyl alcohol 35.0 parts by weight 10% by weight ammonia aqueous solution 7.0 parts by weight
[0391] Thereafter, while the contents of the separable flask were heated and stirred at 40° C., ion-exchanged water was added dropwise at a delivery rate of 8 g / min using a delivery pump.
[0392] Then, when the amount of ion-exchanged water fed reached 580 parts by mass, the dropping of ion-exchanged water was stopped.
[0393] Thereafter, the solvent was removed under reduced pressure to prepare a dispersion liquid (a) of amorphous polyester particles.
[0394] Ion-exchanged water was added to the dispersion liquid (a) to adjust the solid content to 25% by mass, thereby preparing a non-crystalline polyester particle dispersion liquid (a1).
[0395] The volume-based median diameter (d50) of the amorphous polyester particles contained in this amorphous polyester particle dispersion (a1) was measured with Microtrac UPA-150 (manufactured by Nikkiso Co., Ltd.) and was found to be 156 nm.
[0396] (D.2) Preparation of amorphous vinyl resin particle dispersion (b1) A 5 L reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introducing device was charged with 5.0 parts by mass of an anionic surfactant (Dowfax manufactured by The Dow Chemical Company) and 2,500 parts by mass of ion-exchanged water, and the temperature inside the reaction vessel was raised to 75°C while stirring at a stirring speed of 230 rpm under a nitrogen stream.
[0397] Next, a solution in which 18.0 parts by mass of potassium persulfate (KPS) was dissolved in 342 parts by mass of ion-exchanged water was added to the reaction vessel, and the liquid temperature was adjusted to 75°C.
[0398] Further, a mixed solution consisting of the following monomer [3] was added dropwise to the above reaction vessel over a period of 2 hours in the amount shown below.
[0399] <Monomer [3]> Styrene (St) 903.0 parts by mass n-Butyl acrylate (BA) 282.0 parts by mass Acrylic acid (AA) 12.0 parts by mass 1,10-Decanediol diacrylate 3.0 parts by mass Dodecanethiol 8.1 parts by mass
[0400] After the dropwise addition was completed, polymerization was carried out by heating and stirring at 75° C. for 2 hours to prepare a dispersion liquid (b) of amorphous vinyl resin particles.
[0401] Ion-exchanged water was added to the above dispersion liquid (b) so that the solid content was adjusted to 25% by mass, thereby preparing an amorphous vinyl resin particle dispersion liquid (b1).
[0402] The "amorphous vinyl resin" contained in the above-mentioned amorphous vinyl resin particle dispersion liquid (b1) is referred to as "amorphous vinyl resin (B1)".
[0403] The volume-based median diameter (d50) of the amorphous vinyl resin particles contained in the amorphous vinyl resin particle dispersion (b1) was measured with Microtrac UPA-150 (manufactured by Nikkiso Co., Ltd.) and was found to be 160 nm.
[0404] The amorphous vinyl resin (B1) had a glass transition temperature (Tg) of 52° C., a weight average molecular weight (Mw) of 38,000, and a number average molecular weight (Mn) of 15,000.
[0405] (D.3) Preparation of crystalline polyester particle dispersion (c1) (D.3.1) Preparation of crystalline polyester (C1) The following monomer [4] was placed in the following amount into a reaction vessel equipped with a stirrer, a thermometer, a condenser and a nitrogen gas inlet tube, and the atmosphere in the reaction vessel was replaced with dry nitrogen gas.
[0406] <Monomer [4]> Dodecanedioic acid 50 mole parts 1,6-Hexanediol 50 mole parts
[0407] Next, titanium tetrabutoxide (Ti(On-Bu)4) was added in an amount of 0.25 parts by mass per 100 parts by mass of the monomer [4].
[0408] The temperature inside the reaction vessel was raised to 170° C. under a nitrogen gas flow, and the mixture was stirred for 3 hours to carry out the reaction.
[0409] Thereafter, the temperature inside the reaction vessel was further increased to 210° C. over 1 hour, the pressure inside the reaction vessel was reduced to 3 kPa, and the mixture was stirred and reacted under reduced pressure for 13 hours.
[0410] This gave a crystalline polyester (C1).
[0411] The crystalline polyester (C1) had a weight average molecular weight (Mw) of 25,000, a number average molecular weight (Mn) of 8,500, and a melting point of 71.8°C.
[0412] (D.3.2) Preparation of crystalline polyester (C1) particle dispersion Next, the crystalline polyester (C1) and a mixture of the following mixed solution [5] were placed in a separable flask in the amounts shown below, and the mixture was thoroughly mixed and dissolved at 70°C. After that, 8 parts by mass of a 10% by mass aqueous ammonia solution was added dropwise.
[0413] Crystalline polyester (C1) 200 parts by mass
[0414] <Mixed solution [5]> Methyl ethyl ketone 120 parts by mass Isopropyl alcohol 30 parts by weight
[0415] Thereafter, the heating temperature was lowered to 67° C., and ion-exchanged water was added dropwise at a rate of 8 g / min using a pump for delivering ion-exchanged water while stirring.
[0416] Then, when the amount of ion-exchanged water fed reached 580 parts by mass, the dropping of ion-exchanged water was stopped.
[0417] Thereafter, the solvent was removed under reduced pressure to prepare a dispersion liquid (c) of crystalline polyester particles.
[0418] Ion-exchanged water was added to the above dispersion liquid (c) to adjust the solid content to 25% by mass, thereby preparing a crystalline polyester particle dispersion liquid (c1).
[0419] The volume-based median diameter (d50) of the crystalline polyester particles contained in the crystalline polyester particle dispersion (c1) was measured with Microtrac UPA-150 (manufactured by Nikkiso Co., Ltd.) and was found to be 198 nm.
[0420] (D.4) Preparation of release agent particle dispersion (W1) The release agent, surfactant, and ion-exchanged water shown below were mixed in the amounts shown below, and the release agent was dissolved in a pressure discharge homogenizer (Gaulin Homogenizer, manufactured by Gaulin Co., Ltd.) at an internal liquid temperature of 120°C.
[0421] "FNP0090" (release agent) 270 parts by weight "Neogen RK" (surfactant) 13.5 parts by mass Ion-exchanged water: 21.6 parts by weight
[0422] The release agent "FNP0090" (manufactured by Nippon Seiro) is a paraffin wax and has a melting temperature of 89°C.
[0423] Moreover, the above-mentioned surfactant "Neogen RK" (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) is an anionic surfactant.
[0424] Thereafter, the mixture was subjected to dispersion treatment at a dispersion pressure of 5 MPa for 120 minutes, and then at 40 MPa for 360 minutes, followed by cooling to obtain a dispersion liquid (w).
[0425] Further, ion-exchanged water is added to adjust the dispersion liquid (w) so that the solid content becomes 20%, and this is used as a release agent particle dispersion liquid (W1).
[0426] The volume average particle size of the particles in the release agent particle dispersion (W1) was 215 nm.
[0427] (D.5) Preparation of black colorant particle dispersion (1) The following colorants, surfactants, and ion-exchanged water were mixed in the amounts shown below, and pre-dispersed for 10 minutes using a homogenizer (ULTRA-TURRAX T50, manufactured by IKA Corporation).
[0428] "Regal (registered trademark) 330" (coloring agent) 100 parts by weight "Neogen SC" (surfactant) 15 parts by weight Ion-exchanged water 400 parts by weight
[0429] The above "colorant" is carbon black (manufactured by Cabot Corporation). The above surfactant is an anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.).
[0430] Thereafter, a dispersion treatment was carried out for 30 minutes at a pressure of 245 MPa using a high-pressure impact disperser, Ultimizer (manufactured by Sugino Machine), to obtain an aqueous dispersion of black colorant particles.
[0431] Ion-exchanged water was further added to the above-mentioned aqueous dispersion of black colorant particles so that the solid content was adjusted to 15% by mass, and this was used as black colorant particle dispersion (1).
[0432] The volume-based median diameter (d50) of the colorant particles in the black colorant particle dispersion (1) was measured using Microtrac UPA-150 (manufactured by Nikkiso Co., Ltd.) and was found to be 110 nm.
[0433] (D.6) Preparation of toner base particles (1) (Agglomeration / fusion process and maturation process) The dispersion liquid prepared in the above (D.1) to (D.5), a surfactant, and ion-exchanged water were placed in a 4-liter reaction vessel equipped with a thermometer, a pH meter, and a stirrer in the amounts shown below, and 1.0% nitric acid was added at 25°C to adjust the pH to 3.0 to prepare a raw material dispersion liquid.
[0434] Amorphous polyester particle dispersion (a1) 1008 parts by mass Amorphous vinyl resin particle dispersion (b1) 32 parts by mass Crystalline polyester particle dispersion (c1) 160 parts by mass Release agent particle dispersion (W1) 160 parts by weight Black colorant particle dispersion (1) 187 parts by weight "Dowfax2A1" (surfactant) 40 parts by weight Ion-exchanged water 1500 parts by weight
[0435] The above surfactant is an anionic surfactant.
[0436] Thereafter, while dispersing at 3000 rpm using a homogenizer "ULTRA-TURRAX T50" (manufactured by IKA), 100 parts by mass of a flocculant was added dropwise over 30 minutes.
[0437] As the coagulant, an aqueous solution of aluminum sulfate having a concentration of 2% was used.
[0438] After the dropping of the flocculant was completed, the mixture was stirred for 10 minutes to thoroughly mix the raw material dispersion with the flocculant.
[0439] The reaction vessel was then equipped with a stirrer and a heating mantle.
[0440] While adjusting the rotation speed of the stirrer so that the slurry was sufficiently stirred, the temperature inside the reaction vessel was increased at a rate of 0.2°C / min until the temperature reached 40°C.
[0441] After the temperature inside the reaction vessel exceeded 40°C, the temperature was increased at a rate of 0.05°C / min, and the particle size was measured every 10 min using a Coulter Multisizer 3 (aperture diameter 100 μm, manufactured by Beckman Coulter).
[0442] When the volume-based median diameter of the particles in the above raw material dispersion reached 3.9 μm, the temperature was maintained and a mixture of the following amorphous polyester particle dispersion (a1) and a surfactant, which had been mixed in advance, was added to the reaction vessel over a period of 20 minutes.
[0443] <Mixed liquid> Amorphous polyester particle dispersion (a1) 400 parts by mass "Dowfax2A1" (surfactant) 15 parts by weight
[0444] The above surfactant is an anionic surfactant.
[0445] Next, the inside of the reaction vessel was kept at 50° C. for 30 minutes, and then 8 parts by mass of a 20% EDTA (ethylenediaminetetraacetic acid) solution was added to the reaction vessel.
[0446] Thereafter, a 1 mol / L aqueous solution of sodium hydroxide was added to the reaction vessel, and the pH of the raw material dispersion in the reaction vessel was controlled to 9.0.
[0447] Thereafter, the temperature was increased to 85°C at a rate of 1°C / min while adjusting the pH to 9.0 every 5°C, and then maintained at 85°C.
[0448] (cooling process) Thereafter, using "FPIA-3000," the solution was cooled at a temperature drop rate of 10° C. / min when the shape factor reached 0.970, to prepare a toner base particle dispersion (1).
[0449] (filtration, washing and drying processes) Thereafter, the toner base particle dispersion liquid (1) was filtered, thoroughly washed with ion-exchanged water, and then dried at 40° C. to prepare toner base particles (1).
[0450] The toner base particles (1) thus prepared had a volume-based median diameter of 4.0 μm and an average circularity of 0.971.
[0451] (D.7) Addition of external additives The following external additives were added in the amounts shown below to the toner base particles (1) prepared above, and mixed using a Henschel mixer (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.).
[0452] <External additives> Hydrophobic silica (number average primary particle size 12 nm, hydrophobicity degree 68) 1.0 mass% Hydrophobic titanium oxide (number average primary particle size 20 nm, hydrophobicity degree 64) 1.5% by mass
[0453] Thereafter, coarse particles were removed using a sieve with 45 μm openings to prepare "Toner 1."
[0454] E. Preparation of Developer (E.1) Preparation of the developer Carrier 1 prepared in (C.1) to (C.4) above and toner 1 prepared in (D.1) to (D.7) were charged into a V-type mixer in the amounts shown below, and mixed for 5 minutes under normal temperature and humidity conditions to prepare developer 1.
[0455] Carrier 1 100 parts by weight Toner 1 6 parts by weight
[0456] (E.2) Preparation of developers 2 to 14 Developers 2 to 14 were prepared in the same manner as in Developer 1, except that the type of carrier was changed from Carrier 1 as shown in Table V.
[0457] [Table 5]
[0458] F. Evaluation (F.1) Image defects due to charge leakage (Evaluation method) The photoconductor, developer carrier, and developer were installed in the combination shown in Table VI in a commercially available color multifunction printer "bizhub C450i" (manufactured by Konica Minolta, Inc.), and a POD gloss coat (A3 size, 100 g / m2) was printed on the printer under the conditions of V0 = -550 V, Vdc = -400 V, frequency = 4 kHz, and Vpp = 1.5 kV in a normal temperature and humidity environment (temperature 20°C, humidity 50% RH). 2 Ten sheets were printed onto a paper sheet (Oji Paper Co., Ltd.).
[0459] Here, V0 is the surface potential of the photoconductor, Vdc is the DC voltage, and Vpp is the absolute value (|Vp1-Vp2|) of the difference between the minimum value (Vp1) and the maximum value (Vp2) of the AC voltage waveform (see Figure 6). At this time, the DC voltage Vdc is expressed as (Vp1-Vp2) / 2.
[0460] [Table 6]
[0461] The 10 images were visually observed, and the images were evaluated for the occurrence of image defects (black spots) due to leakage according to the following evaluation criteria.
[0462] (Evaluation Criteria) A No image defects due to leakage were observed in any of the 10 sheets. B. Image defects due to leakage were confirmed in at least one of the 10 sheets, and the total number of defective locations was 1 to 3. C. Image defects due to leakage were confirmed in at least one of the 10 sheets, and the total number of defective locations was 4 to 9. D. Image defects due to leaks were confirmed in at least one of the 10 sheets, and the total number of defective locations was 10 or more.
[0463] (F.2) Image density in low temperature and low humidity environments (Evaluation method) After leaving the evaluation machine for one day and night in a low temperature and low humidity environment (10°C / 20%), a 10 cm square solid image was printed and the image density was measured at 10 random locations using a reflection densitometer "RD-918 (manufactured by Macbeth)" and the average density was recorded as the image density. Image density of 1.20 or more was judged to be acceptable for practical use and was rated as passing.
[0464] (Evaluation Criteria) A 1.70 or higher B 1.50 or more and less than 1.70 C 1.20 or more and less than 1.50 D Less than 1.20
[0465] G. Overall Review The silicon contents of the photoreceptors and developer carriers of the examples and comparative examples in the combinations shown in Table VI, and the various values and evaluation results related to the carrier contained in the developer are summarized in Table VII.
[0466] [Table 7]
[0467] The meanings of the symbols in Table VII are as follows: CHMA: Cyclohexyl methacrylate St: styrene MMA: Methyl methacrylate MAA: Methacrylic acid BA: Butyl acrylate CB: Carbon black MgO: Magnesium oxide TiO2: Titanium dioxide *1: Leaked image evaluation *2: Image density in a low temperature and low humidity environment
[0468] As shown in Table VII, unlike the comparative examples, the examples did not receive a rating of "D" for image defects due to charge leakage or image density in a low-temperature, low-humidity environment. This shows that the examples suppress excessive charging of the toner for developing electrostatic images and can obtain good images even in a low-temperature, low-humidity environment. [Explanation of symbols]
[0469] 1. Electrophotographic photoreceptor 10 Developing roller 11 Developing sleeve 12 Magnet Roller 16 Shaft 17 Bearing section 18 Non-drive side flange 19 Drive side flange 100 Image forming device 101 Support for photoreceptor 102 Middle Class 103 Charge generating layer 104 Charge transport layer 105 Outermost layer 110Y, 110M, 110C, 110Bk Image forming unit 111Y, 111M, 111C, 111Bk photoconductor 113Y, 113M, 113C, 113Bk Charging means (charging roller) 115Y, 115M, 115C, 115Bk Exposure means 117Y, 117M, 117C, 117Bk developing means 118Y, 118M, 118C, 118Bk developing roller 119Y, 119M, 119C, 119Bk Cleaning means 131 Intermediate transfer body 133Y, 133M, 133C, 133Bk Transfer means (primary transfer roller) 150 Paper feed conveying means 170 Fixing means 217 Secondary transfer roller (secondary transfer means) SC Original Image Scanner P Transfer material
Claims
1. An image forming system using a two-component developer and an image forming apparatus having at least one of a photoconductor using an aluminum alloy support or a developer carrier using an aluminum alloy developing sleeve, The static resistance value of the carrier contained in the two-component developer is 10 8 Ω・cm or more, 10 12 In the range of less than Ω cm, The silicon content in the aluminum alloy forming at least the support of the photoreceptor or the developing sleeve of the developer carrier is in the range of more than 0.6% by mass and not more than 12.6% by mass.
1. An image forming system comprising:
2. the carrier is made of carrier particles in which at least the surface of a core particle is coated with a coating resin, The coating resin has a structure derived from (meth)acrylate.
2. The image forming system according to claim 1,
3. The coating resin contains at least one of carbon black, magnesium oxide, and titanium dioxide.
3. The image forming system according to claim 2.
4. The exposed area ratio of the core particle to the surface of the carrier particle is within a range of 10.0 to 18.0% with respect to the surface area of the core particle.
3. The image forming system according to claim 2.
5. The silicon content is in the range of more than 0.8% by mass and not more than 12.6% by mass with respect to the total amount of the aluminum alloy forming at least the support of the photoreceptor or the developing sleeve of the developer carrier.
2. The image forming system according to claim 1,
6. The coating resin has a structure derived from an alicyclic (meth)acrylate.
3. The image forming system according to claim 2.
7. The static resistance value of the carrier is 10 8 ~10 10 Within the range of Ω cm 2. The image forming system according to claim 1,
8. An image forming method using a two-component developer and an image forming apparatus having at least one of a photoreceptor using an aluminum alloy support or a developer carrier using an aluminum alloy developing sleeve, comprising: The static resistance value of the carrier contained in the two-component developer is 10 8 Ω・cm or more, 10 12 In the range of less than Ω cm, The silicon content in the aluminum alloy forming at least the support of the photoreceptor or the developing sleeve of the developer carrier is in the range of more than 0.6% by mass and not more than 12.6% by mass.
1. An image forming method comprising:
Citation Information
Patent Citations
Developing roller and developing apparatus using the same
JP2008102502A
Electrophotographic photoreceptor, process cartridge, and electrophotographic device
JP2022132142A